On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests - Jäger, Peter (Zootaxa, 2018)
The genus Systaria Simon 1897 is reviewed in Southeast Asia and eight new species are described: S. lannops spec. nov. from Thailand (female), S. longinqua spec. nov. (male, female) and S. luangprabang spec. nov. (female) from Laos, S. procera spec. nov. (male, female) and S. bregibec spec. nov. (male) from Cambodia, S. bifidops spec. nov. from Malaysia (male), S. panay spec. nov. (female) and S. princesa spec. nov. (male, female) from Philippines. S. elberti (Strand 1913) is illustrated and partly re-described. Informal groups of species are proposed for the first time. Distribution ranges and habitat preferences are mapped.